2018
DOI: 10.1111/wrr.12626
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Chinese powerlessness assessment tool

Abstract: The objectives of this study were to translate the powerlessness assessment tool (PAT) into Chinese, and to evaluate its psychometric performance. The PAT was translated into Chinese and was evaluated in patients with chronic wounds. Mean PAT scores were compared between various wound types to evaluate the scale's power to differentiate wound severity (PUSH score). There were 154 consecutive patients included in this study. All items were included, and the results of item-domain correlation (r ranged from 0.83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The lowest average score of all domains was on well-being. This finding parallels the results of several other studies; 23,26,27 however, Lozano-Platonoff et al 28 found that the lowest CWIS domain score was for social life. Studies on the QoL of patients with chronic wounds help researchers gain a better understanding of the challenges that patients face and the adaptive strategies they use, as well as the factors that relate to QoL among these patients.…”
Section: Discussionsupporting
confidence: 89%
“…The lowest average score of all domains was on well-being. This finding parallels the results of several other studies; 23,26,27 however, Lozano-Platonoff et al 28 found that the lowest CWIS domain score was for social life. Studies on the QoL of patients with chronic wounds help researchers gain a better understanding of the challenges that patients face and the adaptive strategies they use, as well as the factors that relate to QoL among these patients.…”
Section: Discussionsupporting
confidence: 89%
“…The scale has good reliability and validity, with an overall Cronbach α of .96, meaning it is suitable for use with Chinese patients with chronic wounds. 22 The Cronbach α in the present research was .862.…”
Section: Methodsmentioning
confidence: 41%
“…Each item was scored from to 1 (never) to 5 (always), with higher scores corresponding to stronger feelings of powerlessness. The scale has good reliability and validity, with an overall Cronbach α of .96, meaning it is suitable for use with Chinese patients with chronic wounds 22 . The Cronbach α in the present research was .862.…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations